Pulsed Laser Cladding of NiCrBSiFeC Hardcoatings Using Single-Walled Carbon Nanotube Additives - Pascu, Alexandru; Stanciu, Elena Manuela; Croitoru, Catalin; Roata, Ionut Claudiu; Rosca, Julia Mirza; Nicanor, Cimpoesu; Tierean, Mircea Horia; Bogatu, Cristina (Wiley, 2019)
Carbonaceous nanoscale additives present a pronounced inﬂuence on the mechanical properties of both metallic and plastic materials. This paper addresses the fabrication of composite coatings by laser cladding of single-walled carbon nanotubes incorporated by ball milling into a nickel-based powder (NiCrBSiFeC). The coatings were obtained by using the preplaced laser cladding technique on steel substrates. Optical microscopy and SEM microscopy were used to characterise the microstructure reﬁnement of the coatings, and the mechanical behaviour of the coatings has been studied through wear and micro-/nanohardness testin